A Rare Case of Bilateral Empyema in an Infant - Case Report - Arulkumaran Arunagirinathan; Dinesh Kumar Narayana Swamy; Anupriya Raghavan; Balaji Sukumaran (JCDR Research and Publications Pvt. Ltd., 2014)
Infants and children below five years of age are more prone to develop empyema which results due to unrecognised or improperly treated pneumonia. Bilateral empyema in infants are rarely reported. The present case highlights the importance of early interventions by tube thoracostomies and appropriate antibiotics for better outcome.